Fungal Microbiota Dysbiosis and Ecological Alterations in Gastric Cancer - Yang, Ping; Zhang, Xiaoshan; Xu, Rui; Adeel, Khan; Lu, Xiaofeng; Chen, Min; Shen, Han; Li, Zhiyang; Xu, Zhipeng (Frontiers in Microbiology, 2022)
Changes in bacteriome composition has strong association with gastric cancer. However, the relationship between stomach fungal microbiota composition and human host immune factors remains largely unknown. By using high-through ITS2 sequencing, we characterized gastric fungus microbiome among the gastric cancer (n = 22), matched para- gastric cancer (n = 22), and healthy individuals (n = 11). Performed biodiversity analyses to find out diversity within and between the species. Used FUNGuild functional annotation platform to visualize the composition and ecology of gastric cancer -associated fungi and evaluated their potential predictive roles. A total of 4.5 million valid tags were generated and stratified into 1631 operational taxonomic units, 10 phyla and 301 genera were identified. The presence of gastric cancer was associated with a distinct gastric fungal mycobiome signature, characterized by a decreased biodiversity and richness and significant differences in fungal composition. A panel of gastric cancer-associated fungi adequately exhibited diagnostic value. Furthermore, the mRNA levels of cytokines and chemokines were detected and correlated with the specific fungal dysbiosis, indicating the possible mechanism of gastric cancer. This study reveals gastric cancer-associated mycobiome dysbiosis characterized by altered fungal composition and ecology and suggests that the fungal mycobiome might play a role in the pathogenesis of gastric cancer.